Neuronal Redox-Imbalance in Rett Syndrome Affects Mitochondria as Well as Cytosol, and Is Accompanied by Intensified Mitochondrial O2 Consumption and ROS Release - Can, Karolina; Menzfeld, Christiane; Rinne, Lena; Rehling, Peter; Kügler, Sebastian; Golubiani, Gocha; Dudek, Jan; Müller, Michael (Frontiers in Physiology, 2019)
Rett syndrome (RTT), an X chromosome-linked neurodevelopmental disorder affecting almost exclusively females, is associated with various mitochondrial alterations. Mitochondria are swollen, show altered respiratory rates, and their inner membrane is leaking protons. To advance the understanding of these disturbances and clarify their link to redox impairment and oxidative stress, we assessed mitochondrial respiration in defined brain regions and cardiac tissue of male wildtype (WT) and MeCP2-deficient (Mecp2-/y) mice. Also, we quantified for the first time neuronal redox-balance with subcellular resolution in cytosol and mitochondrial matrix. Quantitative roGFP1 redox imaging revealed more oxidized conditions in the cytosol of Mecp2-/y hippocampal neurons than in WT neurons. Furthermore, cytosol and mitochondria of Mecp2-/y neurons showed exaggerated redox-responses to hypoxia and cell-endogenous reactive oxygen species (ROS) formation. Biochemical analyzes exclude disease-related increases in mitochondrial mass in Mecp2-/y hippocampus and cortex. Protein levels of complex I core constituents were slightly lower in Mecp2-/y hippocampus and cortex than in WT; those of complex V were lower in Mecp2-/y cortex. Respiratory supercomplex-formation did not differ among genotypes. Yet, supplied with the complex II substrate succinate, mitochondria of Mecp2-/y cortex and hippocampus consumed more O2 than WT. Furthermore, mitochondria from Mecp2-/y hippocampus and cortex mediated an enhanced oxidative burden. In conclusion, we further advanced the molecular understanding of mitochondrial dysfunction in RTT. Intensified mitochondrial O2 consumption, increased mitochondrial ROS generation and disturbed redox balance in mitochondria and cytosol may represent a causal chain, which provokes dysregulated proteins, oxidative tissue damage, and contributes to neuronal network dysfunction in RTT.